Analisis Pengaruh Pengawasan Dan Keterampilan Kerja Serta Gaji Terhadap Kinerja Karyawan Pada Bengkel Cv. Teguh Harapan Di Kabupaten Berau - Rahman Rahman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The aims of this study were to determine the effect of supervision, work skills, and salaries jointly and partially had a significant effect on employee performance at CV. Teguh Harapan in Berau Regency and analyzing the dominant influence among the variables of supervision, work skills, and salary which have a dominant effect on employee performance at CV. Teguh Harapan in Berau Regency. This type of research was a quantitative study based on hypothesis testing. The population and sample of this study were all employees of CV. Teguh Harapan who had worked for more than 1 year were 100 employees. The data analysis method used multiple linear regressions. The results showed that supervision does not have a significant effect on employee performance. Work Skills already had significant influence on employee performance. Investment had a significant influence on employee performance at CV. Teguh Harapan Workshop in Berau Regency. Kata Kunci: Gaji, Ketrampilan Kerja, Kinerja, Karyawan dan Pengawasan.